Analisis Hukum Atas Klausula Pembatasan Ganti Rugi dalam Syarat Standar Pengiriman JNE Berdasarkan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Anis Sofiatun; I Gde Sandy Satria (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The rapid growth of electronic commerce has increased reliance on courier services, and the legal relationship between shipping companies and consumers is largely governed by standard-form contracts known as Standard Shipping Terms (SSP). One provision that raises legal concern is the limitation of compensation to a maximum of ten times the shipping tariff for uninsured domestic shipments, as applied by PT Tiki Jalur Nugraha Ekakurir (JNE). This study aims to analyze the legal qualification of this limitation-of-liability clause as an exoneration clause and to assess the implementation of the principle of balance between the parties in JNE's Standard Shipping Terms in light of Law Number 8 of 1999 on Consumer Protection. The study employs normative legal research using statute and conceptual approaches, analyzed prescriptively and qualitatively through deductive reasoning. The findings show that the ten-times-tariff compensation limit constitutes an exoneration clause in the form of a limitation of liability that functionally shifts part of the loss arising from JNE's negligence onto the consumer, thereby contravening Article 18 paragraph (1) letter a of the Consumer Protection Law and being null and void insofar as it is applied to proven direct material losses. The implementation of the balance principle in JNE's Standard Shipping Terms is also found to be inadequate, particularly at the stage of contract formation, risk distribution, burden of proof, claim deadlines, and the restriction of dispute-resolution forums.